Thailand : 2009 Article IV Consultation Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Thailand has been in an investment slump since 2006. Political turmoil has led to reduced business confidence and slow private investment growth. The main engine of growth for the economy has been the export sector. The authorities have focused on fiscal measures to stimulate the economy since the second half of 2008. Executive Directors have welcomed the authorities' fiscal stimulus plans, and underscored that timely and efficient implementation of these plans is critical at the current juncture.